Short‐Term Phytoplankton Dynamics During Typhoon Season in and Near the Pearl River Estuary, South China Sea. Issue 2 (14th February 2019) - Qiu, Dajun; Zhong, Yu; Chen, Yongqiang; Tan, Yehui; Song, Xingyu; Huang, Liangmin
Abstract: The effect on phytoplankton dynamics of nutrient inputs from rivers within the highly eutrophic Pearl River Estuary (PRE) in China is well understood. However, the role that typhoons play in enhancing or reducing phytoplankton blooms is less well known. The primary factors controlling phytoplankton dynamics in the PRE in June–July 2009 were determined by coupling satellite remote sensing data with field observations during two successive typhoons: Nangka and Soudelor. The results revealed that the magnitude of chlorophyll a concentration (Chl) near the PRE was controlled by several key factors. (1) Vertical mixing of seawater induced by Typhoons Nangka and Soudelor led to a sudden decrease in Chl and phytoplankton abundance near the PRE, especially in picophytoplankton. (2) Following the typhoon events, increased nutrient availability associated with significant freshwater runoff promoted phytoplankton (especially Synechococcus ) growth, recovery, and blooms in and near the PRE. (3) Increased freshwater input or easterly winds enhanced the extension of highly abundant phytoplankton with brackish water from the estuary into the adjacent nearshore water. (4) Phycocyanin‐rich Synechococcus was endemic and a dominant picophytoplankton group in the estuarial brackish water. We propose a mechanism that describes the interactions of vertical mixing, terrestrial precipitation, freshwater discharge, nutrient inputs, and winds on short‐term phytoplankton dynamics in and near the PRE during typhoon season. Key Points: Typhoons, rainstorms, and wind are crucial parameters influencing short‐term phytoplankton dynamics near the Pearl River Estuary Strong vertical mixing led to sudden decrease in phytoplankton abundance/biomass near the Pearl River Estuary during typhoon season Posttyphoon phytoplankton growth, blooms, and extension in the Pearl River Estuary mostly governed by rivers, nutrients, and wind